Successful extraction of sperm cells after autologous bone marrow transplant: a case report. (4th May 2019) - Jacobsen, Frederik M.; Fode, Mikkel; Sønksen, Jens; Ohl, Dana A.; Jensen, Christian Fuglesang S.
Abstract: We present a case where microdissection testicular sperm extraction (m.T.E.S.E.) was used in a 36-year-old man after non-Hodgkin T-cell lymphoma treated with 2.5 years of chemotherapy, radiation therapy and autologous bone marrow transplantation (B.M.T.). During m.T.E.S.E. two areas of testis tissue with dilated seminiferous tubules were found both containing several sperm cells. These were cryopreserved and subsequently used for intracytoplasmic sperm injection, resulting in a pregnancy. Although the prognosis for sperm retrieval appears to be poor in most men who have undergone B.M.T., our case demonstrates that this is not an absolute conclusion.